Key insights and perspectives from the Food Systems Summit Dialogues and the CAADP 3rd Biennial review process 2023 - Trautman, Sabrina; Chevallier, Romy; Cramer, Laura K.; Gosling, Amanda; Mutamba, Manyewu (African Union Development Agency, 2023)
The 2021 United Nations Food Systems Summit (UNFSS) presented the opportunity to apply an agri-food systems approach to Africa’s existing agricultural and food security efforts. The dialogues provided platforms for governments, businesses, communities and civil society to identify pathways towards resilient and inclusive agri-food systems and to reflect on the benefits of the approach and propose strategies for its mainstreaming. This summary report provides insights and perspectives from the UNFSS dialogues and the Comprehensive Africa Agriculture Development Programme (CAADP) 3rd Biennial Review process. Some of the main findings from the UNFSS dialogues include evidence that countries are adopting diverse approaches to move towards environmentally sustainable food production and consumption, a need to harmonise trade standards and improve access to market information, the generation of high levels of food waste, poor nutritional education and awareness including a lack of dietary diversity, a need for gender and social inclusion with a focus on land tenure and access to resources, a need for improved technologies and innovation and better access to credit and loans for food producers. Key recommendations from the CAADP 3rd Biennial Review include the need to convene national dialogues to discuss the findings of the review, stronger political leadership and commitment to ensure financing and the implementation of key recommendations, a need to strengthen the capacity of regional economic communities to improve mobilisation of Member States, a need to strengthen mutual accountability systems, and the need to integrate the Biennial Review data collection process into existing national monitoring and reporting system, amongst others.